2019
DOI: 10.1016/j.clbc.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Low Plasma IL-8 Levels During Chemotherapy Are Predictive of Excellent Long-Term Survival in Metastatic Breast Cancer

Abstract: Plasma interleukin (IL)-8 levels were monitored in 58 patients with metastatic breast cancer before and during first-line chemotherapy, and changes in the IL-8 levels were correlated with patient survival data. Monitoring plasma IL-8 levels before and during chemotherapy identifies patients with excellent prognosis whose IL-8 levels stay constantly below 16.6 pg/mL. Background: Interleukin (IL)-8 is a proinflammatory cytokine, and high levels of IL-8 are associated with poor prognosis in many malignancies. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 45 publications
3
26
1
Order By: Relevance
“…IL-8 has been observed to be associated with worse disease prognosis in pancreatic cancer, ovarian cancer, breast cancer and NSCLC. [17][18][19][20] Our results contribute to the literature in the era of chemoimmunotherapy.…”
Section: Discussionsupporting
confidence: 61%
“…IL-8 has been observed to be associated with worse disease prognosis in pancreatic cancer, ovarian cancer, breast cancer and NSCLC. [17][18][19][20] Our results contribute to the literature in the era of chemoimmunotherapy.…”
Section: Discussionsupporting
confidence: 61%
“…Interleukin-8 (IL-8) is a known mediator of inflammation and carcinogenesis through its activities related to stem cells, angiogenesis, and metastasis [10,38,68]. High IL-8 levels have been associated with poor prognosis in many malignancies including HCC [10,[68][69][70][71]. Furthermore, induction of IL-8 by Dox was shown to increase the proportion of stem cells in HCC cell lines, while inhibiting the IL-8 signaling pathway decreases stem cell population and attenuates drug resistance [68].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Eggert et al (2016) showed that while SASP of senescent hepatocytes Interleukin-8 (IL-8) is a known mediator of inflammation and carcinogenesis through its activities related to stem cells, angiogenesis, and metastasis [10,38,68]. High IL-8 levels have been associated with poor prognosis in many malignancies including HCC [10,[68][69][70][71].Furthermore, induction of IL-8 by Dox was shown to increase the proportion of stem cells in HCC cell lines, while inhibiting the IL-8 signaling pathway decreases stem cell population and attenuates drug resistance [68]. Our findings also suggest that IL8 might mediate the bridge between senescence and stemness in HCC and can be an important mediator of the cancer-promoting properties of senescent tumor cells.…”
Section: Accepted Articlementioning
confidence: 99%
“…In a separate study, the prognostic significance of plasma HMGB1, IL-6, IL-8, IL-18, MMP-2, MMP-9, glycoprotein YKL-40 and resistin were investigated in 58 metastatic breast cancer patients. In this study, only low levels of IL-8 were associated with increased overall survival, while HMGB1 was not significant [ 188 ].…”
Section: Hmgb1: a Prognostic Biomarker In Cancer Patientsmentioning
confidence: 97%